Sclerotinia sclerotiorum KK-1 isolate from Belarus: pathogenicity factors and glyphosate sensitivity - Kulik, Alena V.; Shukshina, Margarita A.; Evtushenkov, Anatoliy N. (Experimental Biology and Biotechnology, 2020)
In the presence work, mycelial growth, sclerotia formation, polygalacturonase, a-amylase and cellulase activities of a Belarusian fungal isolate Sclerotinia sclerotiorum KK-1 collected from infected сarrot (Daucus carota subsp. sativus) were analyzed. It was established that polygalacturonase was induced by pectin and subject to catabolite repression by glucose. The ability of the isolate to produce oxalic acid, an important factor of pathogenesis, was observed throughout fungus incubation on PDA medium amended with bromophenol blue. Glyphosate (commercial counterpart «Tornado») starting from its level in the medium of 200 mg/L caused a significant inhibition of mycelial growth and sclerotia formation. It was observed that a-amylase and cellulase activities were inhibited by glyphosate unlike polygalacturonase activity.